Effect of chitosan nanoparticles on microtensile bond strength of resin composite to dentin: an in vitro study - Mohamed, Amr Mohsen; Nabih, Sameh Mahoud; Wakwak, Mohamed Ahmed (Brazilian Dental Science, 2020)
Objective: The purpose of this study was to evaluate the effect of chitosan nanoparticles on microtensile bond strength of resin composite to dentin using self etch adhesive after aging. Material and Methods: A total number of 90 freshly extracted, sound human molar teeth. Flat tooth surface was gained after cut of the occlusal surface. Three main groups according to pretreatment of dentin before adhesive application; 0.2 % chitosan, 2.5 % chitosan and no treatment control group. Universal self etch adhesive were applied according to manufacture instruction and 4 mm of Feltik Z250 xt composite. Storage of specimens for 1 day, 3 months and 6 months in 37O C distilled water. After that, the tooth was sectioned to beams of 1 mm x8 mm sticks for microtensile bond strength test using universal testing machine. Scanning electron microscope (SEM) was used to evalute the effect of chitosan nanoparticles on dentin and smear layer. Kruskal-Wallis test was used to compare between the three groups as well as the three aging periods. Dunn’s test was used for pair-wise comparisons. The significance level was set at P ? 0.05. Results: chitosan 0.2% is statistically significant increase in bond strength than chitosan 2.5% and control in one day group. Three months chitosan 0.2 % groups have statistically significant increase in bond strength than chitosan 2.5%. It was found in 6 months that control and chitosan 0.2 % have statistically significant increase in bond strength than chitosan 2.5%. There was statistically significant difference found between the three studied groups regarding bond strength at different storage times . Conclusion: Microtensile bond strength was influenced by different chitosan concentration. Different aging periods had no effect on the microtensile bond strength without application of chitosan and with application of 2.5% chitosan concentration. KEYWORDS Chitosan nanoparticles; Microtensile bond strength; MMPs.